READ ALOUD AS A METHOD FOR IMPROVING LITERACY IN CHILDREN AGED 4-5 YEARS TOWARD GOLDEN INDONESIA: AN EXPERIMENTAL STUDY AT EARLY CHILDHOOD EDUCATION SCHOOLS IN CILEGON CITY - Nurhayati, Is (Jurnal Buah Hati, 2026)
Indonesian society falls into the category of low literacy activity, stagnating at a rate of 37.32. This indicates that there is still an urgent need to improve literacy across all layers of society, including early childhood. Read aloud has become one of the methods to enhance literacy development in early childhood. Thus, the researcher wants to determine the effectiveness of read aloud as a method for improving literacy in children aged 4-5 years at early childhood education (PAUD) schools in the city of Cilegon toward a golden Indonesia. This study employed a pre-experimental design. Data collection techniques included questionnaires, observations, and documentation. Hypothesis testing was conducted using a paired-sample t-test with SPSS 27. Based on the research results, it can be concluded that the calculated t-value (46.142) is greater than the critical t-value (1.666), meaning that the read-aloud method is significantly effective in improving literacy among 4- to 5-year-old children at early childhood education (PAUD) schools in the city of Cilegon, contributing to the “Golden Indonesia” initiative. In practical terms, this study is expected to be of practical benefit to early childhood education (PAUD) teachers in Cilegon City in implementing the read-aloud method, encouraging PAUD institutions to further integrate the read-aloud method into classroom activities, and providing an adequate collection of storybooks. The practice of read-aloud by teachers in schools serves as a form of ongoing literacy stimulation. This study can serve as evidence-based input for policy formulation through the development of more targeted teacher training modules.